AB0524 Biological agents survival comparisons among different rheumatic disease - brazilian register of biological agents in rheumatic diseases - biobadabrasil. (23rd January 2014) - Fafá, B.; Valim, V.; Peçanha, P.; Laurindo, I.; Ranzolin, A.; Hayata, A.; Duarte, Â.; Brenol, C.; Carvalho, H.; Pinheiro, G. C.; Silveira, I.; Pereira, I. A.; et al.
Abstract : Background: Treatment survival of biological agents can be influenced by many factores. It seems to be different between different rheumatic disease. Objectives: To compare the biological treatment survival of the different rheumatic disease to analyze the main causes of treatment discontinuation in patients with rheumatoid arthritis (RA) from the Brazilian Registry – BIOBADABRASIL. Methods: Cohort from Brazilian Society Registry of Biological Therapy in Rheumatic Diseases (BIOBADABRASIL)including 2191 patients, including 1266 (57%) rheumatoid arthritis (RA), 678 (29.5%) spondyloarthritis 247 (12.5%) with others rheumatic disease in use of their first biological agent. They were analyzed at baseline up to 4 years(2008-2012). Sex, age, disease duration, co-morbidities and concomitant treatments at baseline were recorded. Kaplan-Meier estimates, Chi-square, Kruskal-Wallis and Wilcoxon-Mann-Whitney tests, Cox regression analysis were applied when appropriate. Results: Of the 2191 studied patients, 65, 7% were women, 47, 98 ± 13, 85 yrs, 47, 98 ± 13, 85 months of disease duration; 9.5% were smokers; 6.8% had diabetes, 7.8% had hypercholesterolemia. DMARDs at baseline were observed in 77.9% of the patients, 63.9% received methotrexate, 57%, steroids. Regarding biological agents 44.7% (N=979) received infliximab (IFX), 25.7% (N=562) adalimumab (ADA), 21% (N= 460) etanercept (ETA), 4, 1% (N=90) rituximabe (RTX), 2.5% (N=55) tocilizumab (TCZ), 2.1% (N= 45) abatacept (ABA). Retention rate of biological agents was 72.7% of total sample and 72% for patients receiving anti TNF agentes. Survival treatment for Spondyloarthritis patients (41.45 ± 0.5; CI= 40.34 – 42.57) was higher (p≤ 0, 001) compared to RA (37.45 ± 0.46; CI= 36.47 – 38.44) or to other rheumatic disease (39.58 ± 0.98; CI= 37.49 – 41.66). The main cause of disruption was inefficacy (N=277; 46, 1%) followed by adverse events (N= 225; 37.4%) and others (N= 99; 16.5%). Conclusions: Results showed a good anti-TNF survival since 70% continued treatment. Despite being a developing country, the primary cause of interruption was inefficacy and not adverse events. Patients with spondyloarthritis showed better survival for biological therapy. Acknowledgements: Biobadaser; Others Biobadabrasil investigators (Fabiana Britto Goulart, Luís Sérgio Guedes Barbosa, Willian Chahade, Antonio Carlos Ximenes, Marcelo Pinheiro, Mailze Campos Bezerra, José Eduardo Martinez, Mária Fátima Lobato Sauma, Flávio Sztajnbok, Gláucio r. Werner de Castro, Nilzio Antonio da Silvaa, Adriana Maria Kakehasi, Helena Lúcia Alves Pereira, Márcia Bandeira, Mário Newton Azevedo, Cristina Ellert Salomão, Cesar Baaklini, Walber Vieira). Disclosure of Interest: None Declared